Development of brewed coffee substitute from rice grains - Rillo, Ana Regina V.
The main objective of the study is to develop a brewed coffee substitute from rice grains. It is divided into three phases. Phase I is the determination of the optimum roasting time at a constant temperature Range of 250-300°F. This is done through physico-chemical and statistical or sensory analysis. The optimum roasting time determined is used in the determination of the optimum extraction method in phase II. Samples used are subjected once again to physico-chemical and sensory evaluation. Phase II involves the determination of the level of acceptability of the brewed coffee substitute as compared with other commercial brands of brewed coffee in the market. Physico-chemical and sensory tests are used to accomplish this phase. Results of the physico-chemical and sensory/statistical analysis showed that: (1) roasting for 20 minutes at a constant temperature of 250-300°F gave the ideal roast; (2) boiling was the best extraction method; (3) brewed coffee substitute was less accepted than the commercial brewed coffee.